Biocompatibility of A Nano-curcumin Pulpal Paste in Rats - Sahebalam , Rasoul; Sarraf Shirazi, Alireza; Ghazi , Narges; Gifani , Mahshid; Sabzevari, Berahman (Galen Medical Journal, 2024)
Background: This study aimed to assess the biocompatibility of different concentrations of a nano-curcumin pulpal paste in rats. Materials and Methods: Polyethylene tubes containing zinc oxide eugenol (ZOE), Metapex, and 2, 4, 6, and 8 ppm nano-curcumin pulpal paste, and an empty tube as the negative control were implanted in the back of 30 Wistar rats (7 tubes per each rat). The rats were sacrificed after 15, 30, and 60 days (10 rats at each time point). The tissue around the tubes underwent histopathological analysis. After hematoxylin and eosin staining, the specimens were evaluated for presence/absence of necrosis and calcification, number of inflammatory cells, and thickness of soft tissue capsule. Data were analyzed by the Chi-square, Mann-Whitney, and Kruskal-Wallis tests (α=0.05). Results: Necrosis was not seen in any group at any time point. No significant difference existed among the experimental groups regarding calcification at different time points (P>0.05). The fibrotic capsule was thin in all experimental groups at all time points. Rate of inflammation decreased in all experimental groups from day 15 to day 60. Among different concentrations, only 2 ppm concentration of nano-curcumin paste had no significant difference with Metapex and ZOE regarding inflammation at different time points. Conclusion: All tested concentrations of nano-curcumin pulpal paste were biocompatible, compared with the positive controls (ZOE and Metapex); but 2 ppm concentration was the most biocompatible. Within the limitations of this in vitro study, 2 ppm concentration of nano-curcumin may be suggested for further experiments.